Héctor Correa. Quantitative methods of educational planning. Scranton, Pennsilvania : International Textbook Company, 1969. 242 p. - Peña, Raúl de la (Estudios Demográficos y Urbanos, 1971)
HÉCTOR CORREA, Quantitative Methods of Educational Planning, Scranton, Pennsilvania, International Textbook Company, 1969.